Revealing Red Flags of Insurance Fraud: A Case Study Research of PT Jiwasraya Indonesia - Alimirruchi, Wahyu; Chariri, Anis (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
Insurance companies are prone to fraud due to high yield pressures and hence we need to identify certain red flags for fraud detection. This study is descriptive-analytical research that aims at analyzing the red flags of insurance fraud and at finding the strategies to eliminate potential fraud by learning from insurance fraud cases. Using PT Asuransi Jiwasraya (Persero) from 2006 to 2020 as case study research, the finding shows that mega fraud (corruption, asset misappropriation, fraudulent financial statements) occurred during the period. Red flags of improper disclosure are disclaimer opinion from The Audit Board of The Republic of Indonesia, PwC’s adverse opinion, and 2002 and 2004 insolvency. Timing differences red flags are Jiwasraya bought second and third tier shares before the end of the 2019 quarter to be resold on January 2, 2020. Red flags of Jiwasraya’s corruption are indicated by misuse of interest by Jiwasraya’s directors, inappropriate bancassurance, purchase of shares and mutual funds that are more expensive than market prices. Jiwasraya’s red flag in asset misappropriation is shown by the purchase of shares and mutual funds of poor quality using income from the sale of saving plan products. These findings imply that detective, preventive, and repressive strategies are needed to combat insurance fraud in Indonesia.
Keywords: Fraud; Insurance; Red Flags